Alternative Assessments in Online Learning at Elementary Education during Covid-19 Pandemic: The Strenghths and Weaknesses - Arifuddin, Ahmad; Turmudi, Turmudi; Rokhmah, Ummi Nur (International Journal of Elementary Education, 2021)
This study aims to describe the types of online learning assessments that can be implemented at elementary education along with its advantages and disadvantages. This studyemployed a qualitative approach with the literature review. The data were analyzed through reviewing the implementation of online learning assessments at elementary education. In addition, the the results of empiricalstudiesregarding the assessments in online learning were also reviewed. The results of this study showed that online learning assessments that can be implementedin elementary education were formative and summative assessments.It includedcognitive assessments, performance assessments, portfolios, writings and journals, self-assessment and peers-assessments. The use of online learningassessments has many advantages such asthe availability to conduct tests on demand and at any time, provides direct feedback to users, the students’quick access to the test results, and a more accurate measurement ofstudent learning. However, online assessment systems also have several drawbacks, such as students who have low information technology (IT) skills might be disadvantaged. For this reason, in implementing online learning and assessment, teachers and studentsshould master information and communication technology skills.